Effect of Climate Change on Orchids and their Conservation Strategies - Shashidhar, K. S.; Kumar, A. N. Arun (Indian Forester, 2009)
Of the diverse flora and fauna in an ecosystem, epiphytes in general and orchids in particular have a vital role to play in Mutualism. By virtue of their sensitivity to the changes in the climate they provide a forewarning about the impending damages due to these changes and act as bioindicators. Epiphytes constitute ten per cent of the higher plants in tropical forest ecosystem. They provide a niche to many flora and fauna by complimenting the life supporting systems and play a vital role in rainforest hydrology and mineral cycle. Orchids as a group of epiphytes with 900 genera and 30,000 species are sensitive to variations in microclimate and are known as keystone species in the forest ecosystem. Interrelationship of orchids with various biotas in the ecosystem is well documented. Orchid's dependence on other biota and their co existence for several important processes such as pollination, dispersal and sustenance is well known. Natural and man made changes have influenced the climate and in turn the ecosystem through several of its parameters such as rainfall and temperature. One of the direct effects of this is, change in the plant structure and composition. The changes in the climate have also affected sensitive events such as flowering and pollination. This has forced the plant species to shift to more congenial climate for its survival and eventually affecting the coexisting biota. Therefore, before planning any conservation strategies the reasons for threat (especially manmade) to these indicator species must be understood. We believe that, ideal long term orchid conservation approaches must lay emphasis not only on the species but also on its fragile habitat.